Bacterium anitratum and Mima polymorpha infection in Uganda - Lothe, F. (1965)
Eleven cases of infection with Bacterium anitratum and one with Mima polymorpha are described. Microscopically the organisms showed Gram-negative or Gram-variable diplococci with a tendency to form filaments. There appear to be a number of biochemical variants of B. anitratum. Serological cross-reactions with the genus Klebsiella was found. The antibiotic patterns are given and particular attention is drawn to the resistance of the organisms to chloramphenicol.